Study of Molecular Interactions among Esters, Toluene and Aniline using Ultrasonic Technique - P. Vasantharani1, R. Ezhil Pavai1*, S. Renuka1, L. Balu2 (Journal of Experimental Sciences, 2010)
<div style="border-bottom: windowtext 1pt solid; border-left: medium none; padding-bottom: 1pt; padding-left: 0in; padding-right: 0in; border-top: medium none; border-right: medium none; padding-top: 0in; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Abstract The interactions of esters (ethyl acrylate and ethyl benzoate) with common binary of toluene + aniline were studied using ultrasonic velocity, density and viscosity measurements at 303, 308 and 313K. From the experimental data, the acoustical parameters such as adiabatic compressibility (β), free length (Lf), free volume (Vf), internal pressure (πi), acoustic impedance (Z) and their excess values were estimated using standard relation. The results of these parameters are attributed to weak hydrogen bond between solute and solvent molecules. <div style="border-bottom: windowtext 1pt solid; border-left: medium none; padding-bottom: 1pt; padding-left: 0in; padding-right: 0in; border-top: medium none; border-right: medium none; padding-top: 0in; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt;"> Keywords: Ultrasonic study; ternary mixtures; acoustical parameters; molecular interaction 1Department of Physics, Annamalai University, Annamalainagar – 608 002, Tamil Nadu, India; 2Faculty of Engineering and Technology, Annamalai University, Annamalainagar – 608 002, Tamil Nadu, India Please Cite This Article As: R. Ezhil Pavai, S. Renuka, L. Balu and P. Vasantharani. 2010. Study of Molecular Interactions among Esters, Toluene and Aniline using Ultrasonic Technique. J. Exp. Sci. 1(6):21-24